Clinical course and outcomes of supravalvular aortic stenosis in adults - Jolien W Roos-Hesselink; Roland R J van Kimmenade; Annemien E van den Bosch; Michiel Voskuil; Berto J Bouma; Monique R M Jongbloed; Joost P van Melle; Jolanda Kluin; Frederike Meccanici; Adine R de Keijzer; Zoë A Keuning (Open Heart)
Background Supravalvular aortic stenosis (SVAS) is a rare condition with limited data on patients beyond childhood. This study aims to investigate the clinical course and outcomes of SVAS in adults.Methods All adult (≥18 years) patients with SVAS, prospectively registered in the Dutch Congenital Cor Vitia database between 2001 and 2019, were included. Survival and event-free survival were assessed. Evolution of peak velocity was analysed using linear mixed models. Differences in previous operated state, sex and Williams-Beuren syndrome were explored.Results 65 patients were included (age: 23 (IQR: 20, 31) years, 31% female, 46% previous SVAS correction, 47% Williams-Beuren syndrome). The peak velocity was 2.3±1.0 m/s at inclusion. Median follow-up time was 13 (IQR: 10, 17) years. Four patients died (one patient after cardiac surgery, two of non-cardiac causes and in one patient the cause of death was unknown) resulting in a 10-year survival of 95% (95% CI 90% to 100%) and event-free survival of 83% (95% CI 74% to 93%). There were no differences in event-free survival between previous operated state (p=0.2), sex (p=0.48) or Williams-Beuren syndrome (p=0.85). 31 cardiovascular events occurred in 15 patients, with the majority being arrhythmias. All SVAS-related interventions (three surgeries in two patients) occurred in unoperated patients (7 (95% CI 2 to 21)/1000 patient years). Although no patient showed fast progression (≥0.3 m/s/year), the peak velocity evolution over time increased faster in females compared with males (first time spline: 0.8 m/s, p=0.017).Conclusion In adulthood, SVAS patients showed a stable clinical course without rapid progression. While cardiovascular events occurred in this young cohort, they were mostly obsereved in those with additional congenital heart defects, suggesting a more optimistic view for SVAS itself. No significant differences in outcomes were observed in patients with/without Williams-Beuren syndrome. Overall, SVAS tends to follow a more benign course in adulthood compared with childhood, potentially allowing for less intensive follow-up- though follow-up should still be individualised based on associated congenital heart defects and cardiovascular risks.